In-depth review 2024 (Publications Office of the European Union, 2024)
This in-depth review (IDR) analyses the evolution of Romania's vulnerabilities related to large government and external deficits, and possibly newly emerging risks. This year's IDR, which follows the 2024 Alert Mechanism Report (AMR)published in November 2023, assesses the persistence or unwinding of the vulnerabilities identified last year, potential emerging risks, and relevant policy progress and policy options that could be considered for the future.
10.2765/897378
Keywords: Graue Literatur; macroeconomics; euro area; loan; financial stability; financial supervision; household consumption; gross domestic product; inflation; labour market; wage cost; tax system; economic forecasting; Romania; report